Ks. Franciszek Pietrzkiewicz (1858-1929) - Walicki, Bartosz; Zych, Sławomir (Archiwa, Biblioteki i Muzea Kościelne, 2018)
Rev. Franciszek Pietrzkiewicz was born on 5 September 1858 in Zarszyn, in the Sanok district, where he graduated from a folk school. Then he attended gymnasium in Jasło, with a three-year break for military service. In 1884 he entered the Theological Seminary in Przemyśl. On 22 July 1888, he was ordained a priest and became an assistant curate in Miżyniec in the deanery of Mościce (the Przemyśl district). After two years, on 21 September 1890, he was entrusted with the duties of a vicarius dirigens. In 1892 he passed a competitive exam for a parish priest, and from 20 October 1894 onwards, he ran the parish in Miżyniec as an administrator and later as a parish priest. For a short time, Rev. Pietrzkiewicz also managed the parish in Czyszki. The outbreak of World War I brought an end to his pastoral work in Miżyniec. Due to the danger from the Ukrainians, he moved to the parish of Zgłobień in the deanery of Rzeszów. In the spring of 1919, he became a successor of the late parish priest Rev. Mikołaj Dzierżyński. In spite of difficult financial conditions, he managed to complete numerous investment projects in Zgłobień related to the equipment and decoration of the church, the construction of the church tower and the cemetery fence, a presbytery and outbuildings. At the same time, Rev. Pietrzkiewicz was concerned about the living conditions and morality of the parish inhabitants. He also took care of his own priestly formation and supported numerous pious works. In addition, this priest was active in the social sphere. He was, among others, the head of the board in Kasa Stefczyka (a savings and loan association) in Zgłobień, chaired the Farmers’ Association, supported founding the Voluntary Fire Brigade. His efforts were appreciated by church authorities which awarded him expositorium canonicale. He was also an associate dean of Mościce and a school supervisor. Rev. Franciszek Pietrzkiewicz died on 2 January 1929 at the age of 70, 40 years after his ordination.